B-Call: integrating ideological position and voting cohesion in legislative behavior - Toro-Maureira, Sergio; Reutter, Juan; Valenzuela, Lucas; Alcatruz, Daniel; Valenzuela, Macarena (Frontiers in Political Science, 2025)
This paper addresses two central dimensions of legislative behavior: ideological position and voting cohesion. Although both approaches have been widely used to analyze legislative behavior, no unified model currently integrates these dimensions. To fill this gap, the paper proposes a methodology called B-Call, which combines both dimensions by treating votes as random variables. The model is empirically validated using roll-call data from the legislatures of the United States, Brazil, and Chile. The analysis seeks to capture the complexities of voting behavior, resulting in a two-dimensional indicator. This study addresses key gaps in existing legislative voting models, particularly in contexts with limited party control.